Effect of Screentime during School From Home - Yudianita Kesuma (Conferences of Medical Sciences Dies Natalis, 2020)
The COVID-19 pandemic has significantly changed people's lives around the world. Thousands of millions of people around the world must stay at home to protect and prevent Covid-19 transmission. Covid-19 cases in children have also increased even though the prevalence rate is still lower than adult cases.The government through the Ministry of Education and Culture made recommendations during the Covid-19 pandemic to conduct distance / online learning, so that the teaching and learning process can still take place even though you don't have to come to school. This requires a separate adaptation process for the continuity of online learning to run well, with digital media as a learning tool. Screen time or staring at the screen for children has a recommended time limit, because if it is used beyond the safe time it will have a serious impact on the child's health and development. It takes the role of parents, teachers / schools, the community, and policy makers to oversee the process of using digital media in distance learning during the Covid-19 pandemic.In conclusion, the use of digital media during the pandemic is increasing, especially for children, apart from being a medium for distance learning as well as a medium for entertainment. This must be properly monitored by parents, teachers / schools, the community, and policy makers so that the adverse effects of using digital media do not occur according to WHO / IDAI recommendations.